Diagnosis and management of diarrhea in solid‐organ transplant recipients: Guidelines from the American Society of Transplantation Infectious Diseases Community of Practice. Issue 9 (10th April 2019) - Angarone, Michael; Snydman, David R.; ,
Abstract: These guidelines from the Infectious Diseases Community of Practice of the American Society of Transplantation review the diagnosis, prevention, and management of diarrhea in the pre‐ and post‐transplant period. Diarrhea in an organ transplant recipient may result in significant morbidity including dehydration, increased toxicity of medications, and rejection. Transplant recipients are affected by a wide range of etiologies of diarrhea with the most common causes being Clostridioides (formerly Clostridium ) difficile infection, cytomegalovirus, and norovirus. Other bacterial, viral, and parasitic causes can result in diarrhea but are far less common. Further, noninfectious causes including medication toxicity, inflammatory bowel disease, post‐transplant lymphoproliferative disease, and malignancy can also result in diarrhea in the transplant population. Management of diarrhea in this population is directed at the cause of the diarrhea, instituting therapy where appropriate and maintaining proper hydration. Identification of the cause to the diarrhea needs to be timely and focused.